Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
love love
Xem chi tiết
Trần Thị Minh Ngọc
Xem chi tiết
ILoveMath
29 tháng 1 2022 lúc 22:45

undefined

Roger Federer
Xem chi tiết
Nguyễn Lê Phước Thịnh
22 tháng 11 2022 lúc 21:22

\(B=\dfrac{2^{10}\cdot3^8-2^{10}\cdot3^{10}}{2^{10}\cdot3^8+2^{10}\cdot3^8\cdot5}=\dfrac{2^{10}\cdot3^8\left(1-3^2\right)}{2^{10}\cdot3^8\left(1+5\right)}=\dfrac{1-9}{6}=\dfrac{-8}{6}=-\dfrac{4}{3}\)

Thị Thùy Nguyễn
Xem chi tiết
Quân Đặng Anh
17 tháng 4 2017 lúc 18:55

dễ

hết

chỗ

chê

Kudo Shinichi
17 tháng 4 2017 lúc 18:58

\(1-\)\(a,\frac{7}{8}-\frac{2}{3}=\frac{21}{24}-\frac{16}{24}=\frac{5}{24}\)

\(b,\frac{7}{8}-\frac{2}{3}\times\frac{3}{4}=\frac{7}{8}-\frac{1}{2}=\frac{7}{8}-\frac{4}{8}=\frac{3}{8}\)

\(2-\)\(a,\frac{5}{8}-x=\frac{5}{9}\)

\(x=\frac{5}{8}-\frac{5}{9}\)

\(x=\frac{5}{72}\)

\(b,\frac{3}{4}:x=\frac{2}{5}\)

\(x=\frac{3}{4}:\frac{2}{5}\)

\(x=\frac{15}{8}\)

Trần Nhật Quỳnh
17 tháng 4 2017 lúc 19:00

1, Tính:

\(\frac{7}{8}\) - \(\frac{2}{3}\) = \(\frac{21}{24}\) - \(\frac{16}{24}\) = \(\frac{5}{24}\)

\(\frac{7}{8}\) - \(\frac{2}{3}\) x \(\frac{3}{4}\) = \(\frac{7}{8}\) - \(\frac{1}{2}\) = \(\frac{7}{8}\) - \(\frac{4}{8}\) = \(\frac{3}{8}\)

2, Tìm x

\(\frac{5}{8}\)- x = \(\frac{5}{9}\)

           x = \(\frac{5}{8}\)\(\frac{5}{9}\)

           x = \(\frac{5}{72}\)

\(\frac{3}{4}\): x = \(\frac{2}{5}\)

           x = \(\frac{3}{4}\) : \(\frac{2}{5}\)

           x = \(\frac{15}{8}\)

kiune  ( ミ★тєαм ƒαи вιв...
Xem chi tiết
Nguyễn Hoàng Minh
22 tháng 10 2021 lúc 15:30

\(\Rightarrow\left(x-1\right)^2-\left(2x-3\right)^2=0\\ \Rightarrow\left(x-1-2x+3\right)\left(x-1+2x-3\right)=0\\ \Rightarrow\left(2-x\right)\left(3x-4\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{4}{3}\end{matrix}\right.\)

kiune  ( ミ★тєαм ƒαи вιв...
22 tháng 10 2021 lúc 15:33

Nguyễn Hoàng Minh  thank you

thảo nguyên
Xem chi tiết
nthv_.
8 tháng 11 2021 lúc 14:49

\(\left\{{}\begin{matrix}4x^2-12x+9\\x^2+10x+25\end{matrix}\right.\)

๖ۣۜHả๖ۣۜI
8 tháng 11 2021 lúc 14:51

=2x2 - 2.2x.3 + 32

=4x2-12x+ 9

b) =x2+ 2.x.5+52

=x2+ 10x+25

Kim Taehyung
Xem chi tiết
Kudo Shinichi
Xem chi tiết
Lightning Farron
10 tháng 6 2017 lúc 21:11

a)\(x^8+x^4+1\)

\(=\left(x^8+2x^4+1\right)-x^4\)

\(=\left(x^4+1\right)^2-x^4\)

\(=\left(x^4-x^2+1\right)\left(x^4+x^2+1\right)\)

\(=\left(x^4-x^2+1\right)\left(x^2-x+1\right)\left(x^2+x+1\right)\)

b)\(x^{10}+x^5+1\)

\(=\left(x^{10}+x^9+x^8\right)-\left(x^9+x^8+x^7\right)+\left(x^7+x^6+x^5\right)-\left(x^6+x^5+x^4\right)+\left(x^5+x^4+x^3\right)-\left(x^3+x^2+x\right)+\left(x^2+x+1\right)\)

\(=x^8\left(x^2+x+1\right)-x^7\left(x^2+x+1\right)+x^5\left(x^2+x+1\right)-x^4\left(x^2+x+1\right)+x^3\left(x^2+x+1\right)-x\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^8-x^7+x^5-x^4+x^3-x+1\right)\)

Trần Băng Băng
10 tháng 6 2017 lúc 21:35

a) \(x^8+x^4+1\)

= \(x^8+2x^4-x^4+1\)

= \(\left(x^4+1\right)^2-x^4\)

= \(\left(x^4-x^2+1\right)\left(x^4+x^2+1\right)\)

= \(\left(x^4-x^2+1\right)\left(x^4+2x^2-x^2+1\right)\)

= \(\left(x^4-x^2+1\right)\left[\left(x^2+1\right)^2-x^2\right]\)

= \(\left(x^4-x^2+1\right)\left(x^2+1-x^2\right)\left(x^2+1+x^2\right)\)

= \(\left(x^4-x^2+1\right)\left(2x^2+1\right)\)

b) \(x^{10}+x^5+1\)

= ( x10+x9+x8) - (x9+x8+x7) + (x7+x6+x5) - (x6+x5+x4) + (x5+x4+x3) - (x3+x2+x) + (x2+x+1)

= (x2+x+1)(x8 - x7+x5-x4+x3-x+1)